(untitled) (Bangladesh Journal of Nuclear Medicine, 2022)
Background: Numerous researches had illustrated the long-term impact of COVID-19 on thyroid gland worldwide. The aim of this study is to observe similar consequences among Bangladeshi population since there is not much information available. Materials and Methods: A total of 58 adult patients with a mean age of 29.53±9.005 years were studied to observe the long-term effect ( > 6 months to 2 years) of COVID-19 infection, on their thyroid functions. Through convenience sampling, COVID-19 positive patients were selected, excluding any previously known thyroid illness or surgery, other endocrine complaints, pregnancy, COPD or bronchial asthma, hypertension, malignancy, or kidney disease. Thyroid functional status was assessed by quantitative determination of thyroid hormones and autoantibodies. Results: Between a case group of 58 adult COVID-19 survivors and a control group of 27 healthy individuals, there was no significant difference in thyroid hormone levels (FT3, FT4, and TSH). However, two patients developed thyroid toxicity, with increased levels of FT3, FT4 and a decreased level of TSH. Concomitantly, increased levels of thyroid autoantibodies were also observed in two other patients. Additionally, female participants showed significantly lower levels of FT3 and FT4 compared to the control group (p = 0.02 and p = 0.008, respectively). Among all of the COVID-19 survivors, a total of 10 patients (17%) showed deviations from the normal range of thyroid hormones and thyroid autoantibodies. The rest of the 48 patients (83%) revealed no abnormality. Conclusion: Female survivors experienced a significant change in thyroid functional status that lasted longer. However, further research needs to be performed on a larger scale before reaching a conclusion. Bangladesh J. Nuclear Med. 25(2): 93-97, 2022